A model for multi-component droplet heating and evaporation and its implementation into ANSYS Fluent. (January 2018) - Rybdylova, O.; Poulton, L.; Al Qubeissi, M.; Elwardany, A.E.; Crua, C.; Khan, T.; Sazhin, S.S.
Abstract: The main ideas of the model for multi-component droplet heating and evaporation, based on the analytical solutions to the heat conduction and species diffusion equations in the liquid phase, and its implementation into ANSYS Fluent CFD software are described. The model is implemented into this software via User-Defined Functions (UDF). The predictions of ANSYS Fluent with the newly implemented model are verified against the results predicted by the previously developed in-house research code for droplets comprising of a mixture of ethanol and acetone evaporating and cooled down in ambient air.